FEMINISME EKSISTENSIALIS TOKOH KATNISS EVERDEEN DALAM SERIAL FILM THE HUNGER GAMES (ANALISIS SEMIOTIKA ROLAND BARTHES) - Finy Fitrya Basarah (SEMIOTIKA: Jurnal Komunikasi, 2017)
Katniss Everdeen was the main role in film franchise “The Hunger Games” who had done her mission fight against The Capitol. Katniss Everdeen was a girl, who was capable to actualize herself, she knew which one she should choice for her best. This character (girl) that was aware of her freedom made me interested to make a research from existentialist feminism’s side, using semiotic analysis of Roland Barthes that had two significance orders, denotative and connotative, which was in connotative order would be more explored the hidden ideology (Barthes named it mythology). The final conclusion of this research indicated that there was socialist-communist ideology where lower-class citizen (indirectly under Katniss’s order) won the rebellion against government’s injustice.Keywords: Existentialist feminism, Film, Semiotic Analysis of Roland Barthes.